Wastewater-derived organic contaminants in fresh produce: Dietary exposure and human health concerns. (1st September 2022) - Ben Mordechay, Evyatar; Sinai, Tali; Berman, Tamar; Dichtiar, Rita; Keinan-Boker, Lital; Tarchitzky, Jorge; Maor, Yehoshua; Mordehay, Vered; Manor, Orly; Chefetz, Benny
Highlights: Exposure to wastewater-derived contaminants of emerging concern (CEC) was assessed. Crops accounting for ∼70% of the fresh produce consumption were analyzed. For the non-extreme scenarios, hazard quotients for all 58 CECs were lower than 1. Consumption of leafy greens resulted in the highest human exposure to CECs. For the extreme scenario, exposure of ΣCECs reached 85, 700 ng/person per day. Abstract: Irrigation with reclaimed wastewater is a growing practice aimed at conserving freshwater sources, especially in arid and semiarid regions. Despite the apparent advantages to water management, the practice of irrigation with reclaimed wastewater exposes the agroenvironment to contaminants of emerging concern (CECs). In this report, we estimated the unintentional dietary exposure of the Israeli population (2808 participants) to CECs from consumption of produce irrigated with reclaimed wastewater using detailed dietary data obtained from a National Health and Nutrition Survey (Rav Mabat adults; 2014–2016). Human health risk analyses were conducted based on acceptable daily intake (ADI) and threshold of toxicological concern (TTC) approaches. The highest unintentional exposure to wastewater-borne CECs was found to occur through the consumption of leafy vegetables. All analyzed CECs exhibited hazard quotients <1 for the mean- and high-exposure scenarios, indicating no human health concerns. However, for the extreme exposure scenario, the anticonvulsant agents lamotrigine and carbamazepine, and the carbamazepine metabolite epoxide-carbamazepine exhibited the highest exposure levels of 29, 100, 27, 200, and 19, 500 ng/person (70 kg) per day, respectively. These exposure levels exceeded the TTC of lamotrigine and the metabolite epoxide-carbamazepine, and the ADI of carbamazepine, resulting in hazard quotients of 2.8, 1.1, and 1.9, respectively. According to the extreme estimated scenario, consumption of produce irrigated with reclaimed wastewater (leafy vegetables in particular) may pose a threat to human health. Minimizing irrigation of leafy vegetables using reclaimed wastewater and/or improving the quality of the reclaimed wastewater using an advanced treatment would significantly reduce human dietary exposure to CECs. Graphical abstract: Image, graphical abstract